First Report of Nothophoma quercina Causing Brown Spot Disease on 'Huanghua' Pear (Pyrus pyrifolia Nakai) in China - Tang, Xiaomei; Yin, Ruichang; Xiao, Ziwen; Lu, Fen; Zeng, Xiangling; Liu, Lun; Ye, Zhenfeng; Liu, Li; Heng, Wei; Zhu, Li Wu; Jia, Bing (Plant disease, 2023)
Pear (Pyrus L.) is an important fruit tree in China, which has the largest cultivation area and yield in the world (Jia et al. 2021). In June 2022, brown spot symptoms were observed on 'Huanghua' pear (Pyrus pyrifolia Nakai, cv. Huanghua) leaves in the germplasm garden of Anhui Agricultural University (High Tech Agricultural Garden), Anhui, Hefei, China. The disease incidence was approximately 40% according to the percentage of diseased leaves among 300 leaves (50 leaves each were obtained from 6 plants). Initially, small, brown, round to oval lesions appeared on the leaves, the spots were gray in the central, and surrounded by brown to black margins. These spots rapidly enlarged, eventually causing abnormal leaf defoliation. To isolate the brown spot pathogen, symptomatic leaves were harvested, washed with sterile water, surface-sterilized with 75% ethanol for 20 s, and washed 3-4 times with sterile water. Leaf fragments were placed onto PDA medium and incubated at 25°C for 7 days to obtain isolates. The colonies exhibited white to pale gray aerial mycelium and reached a diameter of 62 mm after 7 days of incubation. Conidiogenous cells were characterized as phialides, and exhibited a doliform to ampulliform shape. Conidia displayed various shapes and sizes, ranging from subglobose to oval or obtuse, with thin walls, aseptate hyphae, and a smooth surface. They measured 4.2-7.9 × 3.1-5.5 μm in diameter. These morphologies were similar to Nothophoma quercina as reported previously (Bai et al. 2016; Kazerooni et al. 2021). For molecular analysis, the internal transcribed spacers (ITS), beta-tubulin (TUB2), and actin (ACT) regions were amplified using the primers ITS1/ITS4, Bt2a/Bt2b, and ACT-512F/ACT-783R respectively. The sequences of ITS, TUB2, and ACT were deposited in GenBank (accession numbers: OP554217, OP595395, and OP595396, respectively). A nucleotide blast search revealed high homology with N. quercina sequences: MH635156 (ITS: 541/541, 100%), MW672036.1 (TUB2: 343/346, 99%), FJ426914.1 (ACT: 242/262, 92%). A phylogenetic tree was constructed with ITS, TUB2 and ACT sequences based on neighbor-joining method using MEGA-X software, which showed the highest similarity with N. quercina. To confirm the pathogenicity, the leaves of three healthy plants were sprayed with spore suspension (106 conidia/mL), whereas control leaves were prayed with sterile water. The inoculated plants were covered with plastic bags and cultured in a growth chamber (90% relative humidity) at 25°C. Typical disease symptoms appeared on the inoculated leaves after 7-10 days, whereas no symptoms were observed on the control leaves. The same pathogen was re-isolated from the diseased leaves, according with Koch's postulates. Therefore, based on morphological and phylogenetic tree analyses, we confirmed that the causal organism for brown spot disease was N. quercina fungus (Chen et al. 2015; Jiao et al. 2017). To our knowledge, this is the first report of brown spot disease caused by N. quercina on 'Huanghua' pear leaves in China.